A Sinusoidally Architected Helicoidal Biocomposite. Issue 32 (30th May 2016) - Yaraghi, Nicholas A.; Guarín‐Zapata, Nicolás; Grunenfelder, Lessa K.; Hintsala, Eric; Bhowmick, Sanjit; Hiller, Jon M.; Betts, Mark; Principe, Edward L.; Jung, Jae‐Young; Sheppard, Leigh; Wuhrer, Richard; McKittrick, Joanna; et al.
Abstract : A fibrous herringbone‐modified helicoidal architecture is identified within the exocuticle of an impact‐resistant crustacean appendage. This previously unreported composite microstructure, which features highly textured apatite mineral templated by an alpha‐chitin matrix, provides enhanced stress redistribution and energy absorption over the traditional helicoidal design under compressive loading. Nanoscale toughening mechanisms are also identified using high‐load nanoindentation and in situ transmission electron microscopy picoindentation.